Accuracy of biomicroscopy, ultrasonography and spectral-domain OCT in detection of complete posterior vitreous detachment - Jasmin Zvorničanin; Edita Zvorničanin; Maja Popović (BMC Ophthalmology, 2023)
Abstract Background To evaluate the accuracy of preoperative biomicroscopy (BM), ultrasonography (US), and spectral domain optical coherence tomography (SD-OCT) to determine complete posterior vitreous detachment (PVD) confirmed by intraoperative findings of triamcinolone acetonide-assisted pars plana vitrectomy (PPV). Methods This prospective study included all consecutive patients admitted for surgical treatment of the epiretinal membrane (ERM) and macular hole (MH). The presence of complete PVD was determined one day before PPV using BM, US, SD-OCT. The preoperative findings were compared to the PVD status determined during PPV. Results A total of 123 eyes from 123 patients were included in the study. Indications for PPV included ERM in 57 (46.3%), full thickness macular hole in 57 (46.3%) and lamellar macular hole in 9 (7.3%) patients. Complete PVD during PPV was observed in 18 (31.6%; 95%CI:18.7–49.9) patients with ERM and 13 (19.7%; 95%CI:10.4–33.7) patients with MH. The sensitivity of preoperative BM, US, SD-OCT was 48.4% (95%CI:30.2–66.9), 61.3% (95%CI:42.2–78.2) and 54.8% (95%CI:36.0–72.7) respectively. The specificity of preoperative BM, US, SD-OCT was 81.5% (95%CI:72.1–88.9), 90.2% (95%CI:82.2–95.4) and 85.9% (95%CI:77.0–92.3) respectively. With a prevalence of 25.2% of PVD in our sample the positive predictive value of preoperative BM, US, SD-OCT was 46.9% (95%CI:29.1–65.3), 67.9% (95%CI:47.6–84.1) and 56.7% (95%CI:37.4–74.5) respectively. Conclusion Preoperative BM, US, and SD-OCT showed relatively low sensitivity but also good specificity in assessing complete PVD. A combination of all three diagnostic methods can provide a good assessment of the vitreoretinal interface state.